Shaping a Monastic Identity: Liturgy and History at the Imperial Abbey of Farfa, 1100-1125 - Walter, Barbara R. (Implicit religion, 2008)
The article reviews the book "Shaping a Monastic Identity: Liturgy and History at the Imperial Abbey of Farfa, 1100-1125," by Susan Boynton.